تأثير نمط التربية في إنتاج الحليب عند الماعز الشامي في المنطقة الساحلية من سوريا - حبيب, فؤاد; الخير, خالد مرتضى (Latakia University Journal -Biological Sciences Series, 2013)
تم تنفيذ البحث في أربع مناطق متباينة من الساحل السوري على أربعة أسراب من الماعز الشامي مختلفة الأعداد. تربى بأساليب مغايرة بحسب مفاهيم المربين وحاجاتهم والطبيعة الجغرافية لكل منطقة, إذ بلغ عدد العنوز التي خضعت للدراسة (44) رأس. حُسِب متوسط الإنتاج اليومي من الحليب للعنزة الواحده, والمتوسط الشهري, ومتوسط الإنتاج الكلي لكل سرب خلال موسم الإدرار المقسم إلى مرحلتين (الرضاعة, الإدرار) وكان في الأولى ( 2493,9 – 2238,6 – 1776,6 – 81,6 ) ل بحسب ترتيب الأسراب وأساليب التربية (4 – 2- 3- 1 ), وكذلك في الثانية. ونسبة الإنتاج كانت بمعدل (54,27)% في الأسلوب الأول للسرب الأول وفي الأساليب الأخرى كانت أقل من (50)% وارتفعت عند الأسراب الأخرى ( 55,83 – 54,63 – 50,60 – 45,72 )% وعلى التوالي ( 3- 4 – 2- 1 ), وتبين من خلال التحليل الإحصائي عدم وجود فروق معنوية عند الأسراب الثاني والرابع رغم اختلاف الأسلوبين ووجودها عند السربين الأخرى. وفي المرحلة الثانية كانت الفروق المعنوية موجوده عند الأسراب الأربعة بالتوافق مع أساليب التربية المختلفة. This research was carried out in four different regions on the Syrian coast on four herds of Shami goats different in numbers. These were grown in different ways depending on farmers' concepts and needs, and the geographic location of each region. The number of goats that were studied was (44). The daily average of milk production per goat was calculated, in addition to the monthly average and overall average for every herd during the lactation season which was divided into two phases (Breastfeeding, Lactation) .In the first phase it was (2493,9 – 2238,6 – 1776,6 – 81,6) L ordered by herd and method of breeding (4 – 2 – 3 – 1) and same was in the second phase. The average production rate was (54,27)% in first method of first herd and in other methods was lower than (50)% and increased in other herds (49,39 – 45,36 – 44,16)% respectively (2 –4 – 3 – 1). It was noticed that in the second phase of Lactation the herd of first method retracted to lower than (50)%and rose in other herds (55,83 – 54,63 – 50,60 – 45,72 )% Respectively (1 –2 – 4 – 3). Statistical analysis demonstrated the lack of significant differences in second and forth herd in spite of the different methods used in the other herds, and in second phase statistical analysis was in four herds in accordance with different methods of breeding.